ECCO Guidelines on Therapeutics in Crohn's Disease: Surgical Treatment. (19th November 2019) - Adamina, Michel; Bonovas, Stefanos; Raine, Tim; Spinelli, Antonino; Warusavitarne, Janindra; Armuzzi, Alessandro; Bachmann, Oliver; Bager, Palle; Biancone, Livia; Bokemeyer, Bernd; Bossuyt, Peter; Burisch, Johan; et al.
Abstract: This article is the second in a series of two publications relating to the European Crohn's and Colitis Organisation [ECCO] evidence-based consensus on the management of Crohn's disease. The first article covers medical management; the present article addresses surgical management, including preoperative aspects and drug management before surgery. It also provides technical advice for a variety of common clinical situations. Both articles together represent the evidence-based recommendations of the ECCO for Crohn's disease and an update of previous guidelines.